Metabolic Cystopathy: An umbrella for Diabetic cystopathy and the Obese bladder - Sourabh Sharma; Himanshu Verma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Metabolic syndrome (MetS) is a group of interconnectedconditions that include central obesity, insulin resistance,dyslipidaemia, and hypertension. Although thecardiovascular and endocrine effects of this syndrome arewell-recognized, its impact on the function of the lowerurinary tract is often overlooked. Bladder dysfunctionoftenpresenting as diabetic cystopathy in diabetes- maystem from the wider metabolic environment of MetS. Inthis review, we propose the term Metabolic Cystopathy. Wedetail the pathophysiological connections, clinicalmanifestations, diagnostic methodologies, and treatmentoptions. We stress the importance of multifactorialmanagement approach, including urology, endocrinology,nephrology, dietetics and physiotherapy, to effectivelyaddress this condition. Keywords: Diabetes, diabetic cystopathy, lifestyledisorders, metabolic syndrome, obesity